2021
DOI: 10.5802/crphys.70
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the mechanical properties of nanoparticles: a review

Abstract: Nanoparticles are commonly used in various fields of applications such as electronics, catalysis or engineering where they can be subjected to a certain amount of stress leading to structural instabilities or irreversible damages. In contrast with bulk materials, nanoparticles can sustain extremely high stresses (in the GPa range) and ductility, even in the case of originally brittle materials. This review article focuses on the modeling of the mechanical properties of nanoparticles, with an emphasis on elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 179 publications
(345 reference statements)
1
28
1
Order By: Relevance
“…Two types of core–shell systems are studied, Au 3 Pd 97 with a small core and Au 30 Pd 70 with a larger Au core. The pristine Pd nanocubes show an elastic-to-plastic transition at 4.46% strain (as determined by the abrupt drop in the stress), followed by a seesaw behavior, as expected for an FCC single crystal during indentation . The quasi-elastic stress increases up to 2.5 GPa, creating plastic nucleation events, leading to a 40–60% drop in the stress.…”
Section: Results and Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Two types of core–shell systems are studied, Au 3 Pd 97 with a small core and Au 30 Pd 70 with a larger Au core. The pristine Pd nanocubes show an elastic-to-plastic transition at 4.46% strain (as determined by the abrupt drop in the stress), followed by a seesaw behavior, as expected for an FCC single crystal during indentation . The quasi-elastic stress increases up to 2.5 GPa, creating plastic nucleation events, leading to a 40–60% drop in the stress.…”
Section: Results and Discussionmentioning
confidence: 67%
“…Despise this, as SFs play a crucial role in the deformation of nanosized structures and can be of lengths comparable to the nanoparticle size, approximating partial dislocations to full dislocations can significantly affect the prediction of dislocation generation and propagation . Additional information can be found in a recent review work where different simulation techniques are described for the nanoindentation of nanoparticles . Experimentally, nanoindentation provides a means to study a material’s elastic–plastic and failure behavior by analyzing the initial and final states. , In order to obtain a complete picture of the deformation process, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) are used to perform mechanical experiments in situ at the nanoscale while observing the behavior of the nanostructured sample directly upon subjecting to an external force. For example, in situ TEM nanoindentation experiments have shown softening effects with the decrease in size for nanoscaled metals , below a critical size, that is, an inverse Hall–Petch effect …”
Section: Introductionmentioning
confidence: 99%
“…Compression of small metal FCC nanoparticles has also been studied with simulation methods such as density functional theory (DFT), molecular dynamics (MD), and finite element methods (FEM). 15,16 Among these methods, DFT calculations are usually limited to small numbers of atoms because of the high computational cost, and FEM simulations include continuum assump-tions that may not be valid at the nanoscale, and also cannot provide atomic resolution. 15 MD allows the modeling of nanoparticles of different sizes and geometries at the atomic level, with a reasonable computational cost.…”
mentioning
confidence: 99%
“…15,16 Among these methods, DFT calculations are usually limited to small numbers of atoms because of the high computational cost, and FEM simulations include continuum assump-tions that may not be valid at the nanoscale, and also cannot provide atomic resolution. 15 MD allows the modeling of nanoparticles of different sizes and geometries at the atomic level, with a reasonable computational cost. 17 Previous MD models of metal FCC nanoparticles found that nanoparticles exhibit elasticity at low stress [18][19][20] .…”
mentioning
confidence: 99%
“…Despite being a less studied field, the mechanical behavior of nanoparticles has been a worthy subject of study in the last years due to their unexpected mechanical properties [5][6][7][8][9][10]. Mechanical properties in nanoparticles can be advantageously tailored through several factors such as nanoparticle size [11,12], lattice orientation [13], and surface engineering [14][15][16][17]. All those factors directly impact the elastic and plastic behavior of the nanostructures.…”
Section: Introductionmentioning
confidence: 99%